(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
A total of 2246 medico-legal autopsies were conducted in the mortuary of SRN Hospital of MLN Medical College, Allahabad, during one year study period, out of which nine hundred and fifty (42.29%) cases were due to fatal road traffic accidents (RTA). Only 52.21% of victims could be hospitalized and rest of them (47.79%) either succumbed on the spot or died on way to hospital. 32.42% of RTA victims survived beyond 24 hours and a very small percentage (11.15%) of the hospitalized cases could receive any specific treatment prior death.